Influencia de la fertilización con N, P, K, y cal sobre el rendimiento del maní (Arachis hypagaea L.) cultivado en suelos de terraza alta de los Llanos Orientales. (1978)
Several field experiments were performed to study the effect of liming and the fertilization with N, P and K on the number of pods per plant and yield of peanut (var. Tatui-76) grown on soils of the Eastern Plains. These soils are extremely acid and have low fertility levels. Phosphorus was the most limiting element for growth and yields for the peanut plant. The application of P increased significantly the number of pods per plant and total yields, but had no effect on filling pods. The highest yields (2.070 kg/Ha of peanut in shell) were obtained with 150 kg of 2 5 /Ha. Liming decreased the number of unfilled pods, had no effect on the number of pods but increased yields significantly. The most effective and economic rate of lime was 2.0 ton/Ha. Addition of N and K produced no significant increase in the number of pods, filling of pods and yields